A systematic scoping review of metrics utilized to measure antibiotic consumption in hospital settings - Kandimahforoujaki, Marjan; Patanwala, Kiplin A.; Alffenaar, Jan‐Willem C.; Patanwala, Asad E. (British journal of clinical pharmacology, 2025)
Antimicrobial stewardship (AMS) programs were introduced to promote the judicious use of antimicrobials and to combat antimicrobial resistance. Quantifying antibiotic consumption is an important part of AMS initiatives to achieve these objectives. However, various metrics are available for measuring antibiotic usage, each providing valuable insights but also possessing inherent limitations. The aim of this scoping review was to compare AMS metrics quantifying antibiotic consumption that have been evaluated within hospital settings. It examines the advantages, disadvantages, complexity and components of these metrics to inform their implementation. Four electronic databases, Medline, Embase, Web of Science and the Cochrane Library, were searched to identify articles, where two or more antibiotic consumption metrics were compared in the hospital setting. A total of 4874 articles were screened, with 21 selected for inclusion. The two most commonly used metrics ( n = 19/21 studies) were defined daily dose (DDD) and days of therapy (DOT), which were compared to other metrics. DDD most likely overestimates antibiotic consumption for certain antibiotics such as beta‐lactams and in certain settings such as the intensive care unit. Days of antibiotic spectrum coverage (DASC) and antibiotic spectrum index (ASI) are newer metrics that incorporate antibiotic spectrum and have been compared to DOT. DASC and ASI have shown low correlation with DOT. Reliance on a single metric such as DDD or DOT does not provide an accurate picture of antibiotic use. Hospitals should use DDD or DOT in combination with DASC or ASI to measure antibiotic consumption and the effectiveness of AMS programs.